Between opportunity and reality – bicycle path in promoting safe and eco-friendly urban mobility: A case study of Cugir city - Fechete-Tutunaru Lucian V.; Gaspar Ferenc; Deac Teodora; Filip Nicolae (E3S Web of Conferences)
This study investigated the critical role of bicycle paths in promoting safe and eco-friendly urban mobility using Cugir City, Romania, as a case study. This study analyzes the existing cycling infrastructure, traffic patterns, and public perception of cycling to identify opportunities and challenges in fostering a modal shift towards sustainable transportation. By examining the impact of bicycle paths on safety, traffic flow, and environmental sustainability, this study proposed strategic interventions to enhance Cugir’s cycling network and promote cycling as a viable mode of transport. The findings highlight the importance of continued investment in high-quality cycling infrastructure, traffic calming measures, and public awareness campaigns to create a bicycle-friendly and sustainable urban environment. The study concludes by positioning Cugir as a potential model for other cities seeking to embrace eco-mobility and enhance the quality of life of their residents.